2021
DOI: 10.21203/rs.3.rs-575739/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expression Patterns and Functional Analysis of E3 Ubiquitin Ligase Genes in Rice

Abstract: Background: E3 ubiquitin ligases involve in many processes, containing the response to biotic and abiotic stresses. However, the functions of E3 ubiquitin ligases in rice were rarely studied.Results: In this research, 11 E3 ubiquitin ligase genes were selected and the function analysis was done in rice. These 11 E3 ubiquitin ligase genes showed different expression patterns under different treatments. The BMV:Os06g13870- infiltrated seedlings showed decreased resistance to Magnaporthe grisea (M. grisea) when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Excess ROS are scavenged or detoxified by an efficient antioxidative system that includes both nonenzymic and enzymic antioxidants, such as superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX) [44]. Previously, [45] it was demonstrated that drought stress resistance in VyP5CR transgenic Arabidopsis revealed less efficient scavenging of H 2 O 2 as compared WT lines. In the present study, we observed that TaPUB2 and TaPUB3 transgenic line have a more effective antioxidant defense system and less accumulation of ROS (Figure 6I and Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…Excess ROS are scavenged or detoxified by an efficient antioxidative system that includes both nonenzymic and enzymic antioxidants, such as superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX) [44]. Previously, [45] it was demonstrated that drought stress resistance in VyP5CR transgenic Arabidopsis revealed less efficient scavenging of H 2 O 2 as compared WT lines. In the present study, we observed that TaPUB2 and TaPUB3 transgenic line have a more effective antioxidant defense system and less accumulation of ROS (Figure 6I and Figure S2).…”
Section: Discussionmentioning
confidence: 99%